Modelling foundations and applications : 9th European Conference, ECMFA 2013, Montpellier, France, July 1-5, 2013. Proceedings - Ritter, Tom; Rose, Louis M.; Gorp, Pieter (Lecture Notes in Computer Science,, 2013)
This book constitutes the proceedings of the 9th European Conference on Modelling Foundations and applications, ECMFA 2013, held in Montpellier, France, in July 2013. The 15 papers presented in this volume were carefully reviewed and selected from 51 submissions. They are on all aspects of MDE, including topics such as model querying, consistency checking, model transformation; and model-based systems engineering and domain-specific modeling.